The Sense of Alienation: Romantic versus Modernist - Upadhyay, Bharat Kumar (Cognition, 2021)
Alienation is a focus of modernist writing, but it is a universal fact. As a concept to represent the condition of modern humans, it has evolved with time. Marx talks about alienation, but his concept points to basically man’s dissatisfaction with his socio-economic condition, and it indicates the failures of existing systems to satisfy his needs. The concept of alienation is position in the romantic period, but the modernist concept relates itself to the mentalpsychological ills brought about by man’s condition of being face-to-face with an indifferent universe.